If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3 = 4x + -12 Reorder the terms: 3 + 5x = 4x + -12 Reorder the terms: 3 + 5x = -12 + 4x Solving 3 + 5x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + 5x + -4x = -12 + 4x + -4x Combine like terms: 5x + -4x = 1x 3 + 1x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 3 + 1x = -12 + 0 3 + 1x = -12 Add '-3' to each side of the equation. 3 + -3 + 1x = -12 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = -12 + -3 1x = -12 + -3 Combine like terms: -12 + -3 = -15 1x = -15 Divide each side by '1'. x = -15 Simplifying x = -15
| t^3-5t^2-36t=0 | | 56=16+2w | | x+1.66666667=.8333333333x | | 18-a=a | | 8y+5=3y+25 | | 2x+23=5 | | 5b-16=99 | | x+3-4=-6 | | 0-3y=32 | | 5c-10=80 | | 2(3n-4)=(4n+2)+9 | | 16g+-28=1 | | 40x^3-25x^2+8x-5=0 | | 2s+5=53 | | 8(2n-4)=(4n+7)+4 | | 6w^2-9=33 | | 7(x+(-5))=14 | | 7y+3(y-5)=3(y+1)-2 | | x-20=-100 | | x+20=-100 | | -5(t-5)+8t=9t-1 | | 312x-143x=428 | | (x-1)(x-5)(x-6)=0 | | 864+.8xy=y | | 5x-8x=-5 | | 27+5=19 | | (2h-6)/6=2/3 | | 0.4b=-2 | | .40x+.20(30)=.20(102) | | 9x-2(x+1)=12 | | 0=(3x-8)*lnx | | n+8=16-4 |